Rekonstruksi Paradigma Penegakan Hukum Tindak Pidana Korupsi Di Bidang Bisnis - Mashuril Anwar; Besti Lilyana; Dinda Anna Zatika; Destu Rizky Syahputra (Mahesa Research Center, 2023)
This article aims to evaluate the law enforcement paradigm for criminal acts of corruption in the business sector. The problem focuses on law enforcement against criminal acts of corruption in the business sector in Indonesia today, as well as the ideal construction of overcoming criminal acts of corruption in the business sector. In order to answer these problems, this research uses a normative approach with qualitative analysis. Based on the results of the investigation and discussion, this study concludes that law enforcement against criminal acts of corruption in the business sector in Indonesia currently tends to be formally legalistic. Such law enforcement results in less than optimal recovery of state losses and makes the state